ChemInform Abstract: Synthesis of Isoxazolidine‐Fused Eight‐Membered Heterocycles via an Intramolecular Nitrone—Alkene Cycloaddition. Issue 25 (5th June 2015) - Zhu, Tong; Xiang, Jinbao; Liu, Zhenyu; Dang, Qun; Bai, Xu
Abstract: Novel tricyclic eight‐membered‐ring scaffolds fused by both isoxazolidine and pyrimidine rings are synthesized by an intramolecular nitrone‐alkene cycloaddition.